Pengaruh Komunikasi Pemasaran dan Kualitas Pelayanan Terhadap Keputusan Pembelian “Mie Niraja“ - Wina Afrilia Zahra; Puji Isyanto; Neni Sumarni (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this research is to determine the influence of Marketing Communication and Service Quality on purchasing decisions at Mie NiRaja . The research population consisted of one hundred people selected from those who participated in the Mie NiRaja consumer survey. The research sample is defined as individuals who purchase Mie NiRaja MSMEs. The Lemeshow technique is used in the sample receipt process as preparation for testing. The study in question uses a quantitative methodology. For data collection purposes, this technique uses a questionnaire as a strategy. The methods used in the data analysis process are known as multiple regression and descriptive analysis. Research findings show that the discussion of Marketing Communications and the Quality of Service provided has a significant influence on the decision-making process that occurs throughout the purchasing process. In addition, the decision-making process does not consider these aspects important for meeting the requirements. It is important to note that the output of the coefficient of determination of communication and service quality has a major influence on the decision-making process. It is important to note that this impact is visible. Based on the magnitude of the F test results, this research shows that the quality of communication and service can influence purchasing decisions. Therefore, it is acceptable to believe that X1 and X2 have an equal influence on the final decision taken by consumers. Based on the research results, it can be concluded that Mie NiRaja purchasing decisions are significantly influenced by marketing communications, both partially and simultaneously. This impact is strong and statistically significant. As a consequence of the findings of the Communication Management Study, purchasing choices may be significantly impacted. Because MSME Mie NiRaja provides an appropriate level of customer service quality, it is guaranteed that customers will return again for further transactions in the future. The next step for MSME Mie NiRaja is to carry out an advertising campaign to measure the level of consumer interest in buying its products